Implementation of the School Literacy Movement Before Teaching and Learning Activities at Middle School - Anjani, Aprilia Ika; Maryanti, Rina (ASEAN Journal of Educational Research and Technology, 2023)
The purpose of this study is to determine the effect of the implementation of the School Literacy Movement before teaching and learning activities began on the reading habit of students at Kartika XIX-2 Middle School Bandung, Indonesia. This research is a type of qualitative research that uses a descriptive approach. The research was conducted in three stages: (1) Distribution of pre-educational questionnaires; (2) Education related to literacy and implementation of the School Literacy Movement; and (3) Dissemination of post-education questionnaires. The subjects in this study are students of Kartika XIX-2 Middle School, as many as 10 students. Based on the results of the study, there is an increase in students' interest in reading before and after the implementation of the School Literacy Movement at Kartika XIX-2 Middle School as many as 10% of respondents, and 40% of respondents stated that their interest in reading had increased. In general, students at Kartika XIX-2 Middle School have realized that reading is important. However, this level of awareness is not matched by the awareness of students to implement reading culture as one of the routines shown in the number of respondents is only 10% who make reading a routine.